A Macroscopic Exploration of the Ideoscape on Exosomes for Bone Regeneration - Maria Teresa Colangelo; Marco Meleti; Stefano Guizzardi; Carlo Galli (Osteology)
Background: Exosomes, nanoscale extracellular vesicles, play a crucial role in tissue physiology and regeneration. This study uses infometric techniques to explore the structure of exosome-based tissue and bone regeneration research. Methods: We applied BERTopic, an advanced topic modeling algorithm, to a comprehensive corpus of the scientific literature on exosomes and tissue regeneration, identifying key themes such as stem cell studies, tissue healing, and regenerative applications, with orthopedics and dentistry emerging as dominant subfields. To further investigate the ‘ideoscape’, i.e., the conceptual landscape that maps how ideas, methods, and themes are interconnected across the field, we extracted significant concepts from abstracts using GPT 3.5 turbo and created knowledge graphs. Results: Our analysis revealed rapid growth in the field of dental stem cell regeneration, which has outpaced other bone regeneration topics by twofold. This analysis highlighted central themes such as periodontal stem cells and their cellular processes—proliferation, migration, and differentiation—along with their clinical applications. Our approach provided a clear visualization of the field’s intellectual structure, showing how emerging topics are interconnected. Our findings offer a comprehensive view of the evolving trends in exosome-based bone regeneration, revealing not only the most active research areas but also gaps and opportunities for further investigation. Conclusions: This study exemplifies the utility of combining topic modeling with knowledge graph creation to map research trends, offering a flexible and largely automated tool for researchers to explore the vast bodies of literature and guide future research directions.